The philosophy of Keynes's economics : probability, uncertainty and convention - Runde, Jochen, 1959-; Mizuhara, Sohei, 1969- (London ; New York : Routledge, 2003)
John Maynard Keynes is undoubtedly the most influential Western economist of the twentieth century. His emphasis on the nature and role of uncertainty in economic thought is a dominant theme in his writings. This book brings together a wide array of experts on Keynes' thought such as Gay Tulip Meeks, Sheila Dow and John Davis who discuss, analyse and criticise such themes as: Keynesian probability and uncertainty the foundations of Keynes' economics the relationship between Keynes' earlier and later thought
Includes bibliographical references (p. [252]-263) and index.
oif 04/02/14
Loan
Keywords: Keynesian economics; Probabilities; Uncertainty